2020
DOI: 10.1029/2020jf005729
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Eco‐Geomorphologic Feedback of Coastal Marsh Under Sea Level Rise: Vegetation Dynamic Representations, Processes Interaction, and Parametric Sensitivity

Abstract: Coastal marshes are unique landscapes that connect terrestrial and aquatic systems and provide important ecosystem services, such as sustaining wildlife habitats, protecting shorelines, attenuating floods, storing carbon, and filtering contaminants (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 97 publications
2
14
0
Order By: Relevance
“…Zhang et al. (2020) evaluated the topographic outcomes from these three vegetation schemes and found that all of the schemes predicted a higher elevation increase near the ocean boundary and a lower increase landward. However, these schemes also showed differences in marsh elevation relief and unvegetated‐vegetated ratio.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al. (2020) evaluated the topographic outcomes from these three vegetation schemes and found that all of the schemes predicted a higher elevation increase near the ocean boundary and a lower increase landward. However, these schemes also showed differences in marsh elevation relief and unvegetated‐vegetated ratio.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other schemes to represent the relationship between vegetation biomass and inundation level for different marsh landscapes, such as the Spartina-nonlinear function (Mariotti & Fagherazzi, 2010) and mixed vegetation species linear function (D'Alpaos et al, 2007). Zhang et al (2020) evaluated the topographic outcomes from these three vegetation schemes and found that all of the schemes predicted a higher elevation increase near the ocean boundary and a lower increase landward. However, these schemes also showed differences in marsh elevation relief and unvegetated-vegetated ratio.…”
Section: Uncertainties and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is contrary to the structure of many existing empirical and physical models. Many models either presume processes causing autocompaction operate solely on organic material through decomposition (For example, Zhang et al, 2020), are implicitly incorporated in models of net surface elevation change (Morris et al, 2002;Rogers et al, 2012), or apply a constant rate of autocompaction irrespective of tidal position (For example, Marani et al, 2013). There are exceptions: the WARMER (Swanson et al, 2014) model includes parameters of mineral sediment accretion, organic matter addition and decomposition, and compaction; and OIMAS-N (Mudd et al, 2009) includes parameters of mineral and organic matter addition, decay of carbon pools and compaction.…”
Section: Processes Influencing Morphodynamicsmentioning
confidence: 99%
“…Organic matter accretion may also be expressed as a function of accommodation space, either linearly (D'Alpaos et al, 2007), or as a second-order polynomial with peak productivity delimited by the vertical distribution of vegetation (Morris et al, 2002). However, there is less agreement on attribution of the post-depositional behavior of mineral and organic matter in substrates (Wiberg et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%